SmaCH: an infrastructure for smart cultural heritage environments. (2017) - Chianese, Angelo; Piccialli, Francesco
Cultural heritage represents a worldwide resource of inestimable value, attracting millions of visitors every year to monuments and museums. Fundamental aspects of this resource to be investigated are its promotion and people enjoyment. Indeed, to achieve an enjoyment of a cultural space that is attractive, it is necessary to realise ubiquitous solutions for users' interaction to enrich their visiting experience and improve the knowledge transmission process. Thanks to ICT technologies, it is possible to shorten the distance between a cultural site and its visitors, and reestablish to them the truly educational role which provides the opportunity to produce new experiences of knowledge transmission. In this paper, we present a service-oriented infrastructure aimed to transform cultural heritage sites into smart environments. Following the Internet of Things paradigm, the proposed infrastructure relies on the integration of a wireless sensor network (WSN) with Wi-Fi and Bluetooth technologies to identify, locate and support users.